2012
DOI: 10.1021/bm300250r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Biopolymer Created from the Self-Assembly of a Designed Protein Containing a Four-Helix Bundle Forming Motif

Abstract: A protein hydrogel system based on the assembly of a four-helix bundle motif was proposed and synthesized by genetic engineering methods. This new polypeptide, named GBH1, consists of identical amphipathic helices of 22 residues in length oriented in opposite fashion to one another at each end of a polypeptide with a total length of 227 amino acids. The middle portion of the polypeptide (residues 79-147) is an unstructured random coil. The region between the amphipathic and unstructured segment is an α-helical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…8−10 The first Z-based selfassembled hydrogel was developed by Petka et al, 11 and since then, further research in this area has resulted in additional examples being reported. 8,9,12 Despite this, further optimization is still required for real applications. For example, the instability of these hydrogels has always been a handicap, presumably due to the highly hydrophilic environment created by the aqueous media contained within the hydrogel and, in many cases, gel formation has been qualitatively assessed, and with just a few exceptions, quantitative measurement using rheological methods has proved elusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8−10 The first Z-based selfassembled hydrogel was developed by Petka et al, 11 and since then, further research in this area has resulted in additional examples being reported. 8,9,12 Despite this, further optimization is still required for real applications. For example, the instability of these hydrogels has always been a handicap, presumably due to the highly hydrophilic environment created by the aqueous media contained within the hydrogel and, in many cases, gel formation has been qualitatively assessed, and with just a few exceptions, quantitative measurement using rheological methods has proved elusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One example is Ac‐LIVAGK (LK 6 ). Due to its shortness, these peptides should be a cheaper alternative to other protein‐22, 23 or peptide‐based matrices with longer sequences, e.g., RADA‐1624 (PuraMatrix™), MAX125–27 and others 28, 29…”
mentioning
confidence: 99%
“…50 Depending on the coiled-coil sequence used, multiple unfolding transitions may also be observed, suggestive of intermediate states between fully aggregated and fully disordered with a lower degree of aggregation. 51 Cylindrical aggregates identified by SAXS for tetrameric coiled-coils persist above the dilute solution coiled-coil melting temperature, further indicating that the dissociation transition may be concentration dependent. The mechanical properties of coiled-coil and other associating protein hydrogels show rheology typically for physically associating polymer gels (Fig.…”
Section: Physical Gels With Protein-associating Domainsmentioning
confidence: 99%